Solvent Molecular Design to Regulate the Intercalation Behavior in Ether Electrolyte for Stable Graphite Anodes in Potassium‐Ion Batteries. Issue 10 (12th July 2022) - Wang, Danni; Du, Xiaoqiong; Zhang, Biao
Abstract : It has been widely recognized that ether electrolytes show great advantages in building robust solid–electrolyte interphases (SEIs) for stable anode performance. However, its extension to the graphite electrode is hampered by the ether solvent cointercalation, leading to a lower capacity and higher potential than those in ester counterparts having neat cation insertion. Herein, the ether solvent molecules by optimizing the O/C atomic ratio through tailoring the end group and chain length are screened. Such a modification alters the solvation strength between K ions and the solvent, which dictates the intercalation behavior in graphite. In particular, an ethylene glycol diethyl ether‐derived electrolyte is developed, which prevents the solvent cointercalation and induces the formation of binary intercalation compound KC8 . Meanwhile, the novel ether electrolyte helps build a uniform and robust SEI, significantly boosting the rate capability and long‐term stability of graphite anode. This study resolves the dilemma of ether electrolyte in realizing the stable and high‐capacity graphite anode for facilitating its application in potassium‐ion batteries. Abstract : The solvation strength in ether electrolyte can be controlled by the O/C atomic ratio in the solvent molecule. A unique ether solvent ethylene glycol diethyl ether is proposed for graphite anode. It benefits the stable solid–electrolyte interphase formation while preventing solvent cointercalation in common ether‐based electrolytes.